Caracterização bromatológica de espécies com potencial forrageiro disponíveis para ruminantes no semiárido - SOUZA, Julyana de Sena Rodrigues (2014)
Diversity of foods available for feeding ruminants in semiarid should be considered and used as a positive factor in the animal production. However, the goal of this reserach was to assess and describe the nutritional value of these plant species: spineless cactus (Napalea cochenilifera Salm - Dyck); xiquexique (Pilosocereus gounellei, A. Weber ex K. Schum ex Bly Rowl...); facheiro (Pilosocereus pachycladus Ritter); mandacaru (Cereus jamacaru DC.); coroa-de-frade (melocactus bahiensis Br Et Rose Werderm..); quipá (Opuntia inamoene K. Schum.); and caroá (Neoglaziovia variegata Mez.), from the chemical composition, fractionation of carbohydrates and nitrogen compounds, parameters of degradation and ruminal fermentation. The samples were collected, with four replicates per species, the Development and Dissemination of Rural Hinterland of Alagoas Technology Station, located in Piranhas, Alagoas State. Fractionation of carbohydrates and nitrogen compounds was carried out based on the Cornell Net Carbohydrate and Protein System (CNCPS). It used the technique in automatic vitro gas production with the system ANKOMRF Gas Production System ® for the food prediction fermentation. The cacti species have low dry matter content, justified by morphology and efficiency in accumulating water. Facheiro species (153.96 g / kg DM) and coroa-de-frade (113.23 g / kg DM) had the highest crude protein. Caroa stood out as the species with the highest levels of neutral detergent fiber. Considering the fractionation of carbohydrates, A + B1 fraction it stands for spineless cactus (921,91 g / kg CHO); quipa presented the higher levels for the B2 fraction, and for the fraction C, caroá mandacaru stood out . In relation to nitrogenous compounds fractions, facheiro and coroa-de-frade showed higher contents of A fraction; to B1 + B2 fraction xique-xique and caroá has the highest concentrations; as the B3 fraction spineless cactus and mandacaru. Fraction C was higher in quipa and caroá species. The ruminal fermentation parameters were consistent with the proportions of the fractions of carbohydrates as well as the content of nitrogen compounds.